Kritik atas Iman - Muhammad Anwar Firdausi (el Harakah: Jurnal Budaya Islam, 2006)
In the preceding discussion the term "faith" has been used in a variety of senses. We have used the term to refer to an assumption, conviction and attitudes which the believer brings to the evidence for and against religious truth. It also refers to the commitment and subjective preferences of people in general. Faith is all of these, though this must not be taken as an implication. There is no significant difference between the various kinds of faith. In a sense, every person has faith; everyone has deep-rooted assumption, convictions and attitudes which color what counts as evidence for him and how that evidence is interpreted. This is the kind of faith which one brings to the evidence. Insofar as beliefs are reflected in action, and people must make choices, everyone also has faith in the sense of commitments which may or may not be informed by rational reflection. Dalam diskusi sebelumnya istilah "iman" telah digunakan dalam berbagai pengertian. Kami telah menggunakan istilah tersebut untuk merujuk pada asumsi, keyakinan dan sikap yang dibawa oleh orang percaya kepada bukti dan kebenaran agama. Ini juga mengacu pada komitmen dan preferensi subyektif orang pada umumnya. Iman adalah semua ini, meski ini tidak boleh dianggap implikasinya. Tidak ada perbedaan yang signifikan antara berbagai jenis iman. Dalam arti tertentu, setiap orang memiliki iman; setiap orang memiliki asumsi, keyakinan, dan sikap yang mengakar yang mewarnai apa yang dianggap sebagai bukti baginya dan bagaimana bukti itu ditafsirkan. Inilah jenis iman yang dibawa seseorang ke bukti. Sejauh kepercayaan tercermin dalam tindakan, dan orang harus membuat pilihan, setiap orang juga memiliki keyakinan akan komitmen yang mungkin atau mungkin tidak diinformasikan oleh refleksi rasional.